Efficient strong privacy protection and transferable attribute-based ticket scheme - Huamin FENG; Rui SHI; Feng YUAN; Yanjun LI; Yang YANG (Tongxin xuebao)
To solve the problems of efficiency, flexibility, and privacy protection faced by electronic tickets, an efficient and transferable attribute-based ticket scheme with strong privacy protection was proposed.Firstly, a ticket issuing algorithm based on attribute disclosure was constructed by combining attribute-based credentials and set commitment.Secondly, the structure-preserving signature on equivalence class and dynamic malleable signature were used to reduce the computational complexity of the ticket issuance, and the ticket transfer and ticket verification with constant complexity were realized.In addition, to prevent the possibility of malicious verifiers guessing user information according to the seller’s identity, the scheme not only realized the anonymity of the user, but also realized the anonymity of the seller in the ticket verification for the first time.Finally, the security definition of the scheme was given, and its security was reduced to either well-known complexity cryptography assumptions or the security of proven cryptography primitives.Comparison and experimental results demonstrate that the proposed scheme is flexible and efficient.